Is it all in the heart? Myocardial injury as major predictor of mortality among hospitalized COVID‐19 patients. Issue 2 (2nd August 2020) - Harmouch, Farah; Shah, Kashyap; Hippen, John T.; Kumar, Ashish; Goel, Harsh
Abstract: Coronavirus disease 2019 (COVID‐19) is an infection caused by the virus SARS‐CoV‐2, and has caused the most widespread global pandemic in over 100 years. Given the novelty of the disease, risk factors of mortality and adverse outcomes in hospitalized patients remain to be elucidated. We present the results of a retrospective cohort study including patients admitted to a large tertiary‐care, academic university hospital with COVID‐19. Patients were admitted with confirmed diagnosis of COVID‐19 between 1 March and 15 April 2020. Baseline clinical characteristics and admission laboratory variables were retrospectively collected. Patients were grouped based on mortality, need for ICU care, and mechanical ventilation. Prevalence of clinical co‐morbidities and laboratory abnormalities were compared between groups using descriptive statistics. Univariate analysis was performed to identify predictors of mortality, ICU care and mechanical ventilation. Predictors significant at P  ≤ .10 were included in multivariate analysis. Five hundred and sixty patients were included in the analysis. Age and myocardial injury were only independent predictors of mortality, in patients with/without baseline co‐morbidities. Body mass index, elevated ferritin, elevated d‐dimer, and elevated procalcitonin predicted need for ICU care, and these along with vascular disease at baseline predicted need for mechanical ventilation. Hence, inflammatory markers (ferritin and d‐dimer) predicted severe disease, but not death. Highlights: Age and myocardial injury, as indicated by an elevated troponin are independent predictors of mortality, irrespective of presence or absence of underlying cardiac risk factors. Myocardial injury is fairly common at presentation among patients requiring hospitalization for COVID‐19, about 23% incidence among those with underlying medical illness, and 13.8% among those without. Inflammatory markers predicted need for ICU care and mechanical ventilation, but not death.